Experimental research and simulation analysis of 3D printed dissimilar metals - Mulyadi, Evelyn (Nanyang Technological University, 2023)
With the help of Computer Aided Design by Solidworks, Fusion 360 software and 3-Dimensional object scanners, Additive Manufacturing enables production of objects with accurate geometry and dimensions. Additive Manufacturing is a process where the products are printed layer-by-layer, unlike traditional manufacturing that may require manual machining and other tools to remove extra material. Some examples of Additive Manufacturing are Binder Jetting, Directed Energy Deposition, Material Extrusion, Laser Powder Bed Fusion, Sheet Lamination, Vat Polymerisation, Directed Energy Deposition-Arc, Selective Laser Sintering, Selective Laser Melting.